Prevalence and Morphological Identification of Eimeria Species on Bali Cattle in Sumbawa District, West Nusa Tenggara - Pradana, Munawer; Kurniawan, Muhammad Ahdi’; Berliana, Erprinanda Galuh; ‘Ilmi, Laily Ulya Nurul; Haddar, Mariyam Al; Dharmawibawa, Iwan Doddy (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to determine the prevalence and morphological identification of Eimeria spp. from Bali cattle feces on traditional farms in Sumbawa District. A total of 300 samples were identified and 238 samples were positive, resulting in a prevalence of Eimeria spp. of 79.33%. Based on age category, the highest prevalence of Eimeria spp. was found in cattle aged 6 months-2 years (88.76%; 79/89), followed by cattle aged <6 months (88%; 88/100) and the lowest prevalence in cattle aged >2 years (63.96%; 71/111). Female Bali cattle had the highest prevalence of Eimeria spp. (80.55%; 145/180) than male Bali cattle (77.50%; 93/120). Based on livestock systems, the highest prevalence of Eimeria spp. was found in semi-intensive (89.15%; 74/83), then extensive (80.76%; 105/130) and the lowest in intensive (67.81%; 59/87). Six different Eimeria species were identified: E. bovis (33.19%), E. auburnensis (21.42%), E. zuernii (15.96%), E. alabamensis (12.18%), E. ellipsoidalis (10.50%), and E. canadensis (6.72%). Preventing and controlling coccidiosis infection in cattle can be done with good hygiene management.